The 2019 General Elections and the Future of Democracy in Nigeria - Anyalebechi, Shammah Mahakwe (International Journal on Integrated Education, 2022)
This paper takes a critical look at the February/ March 2019 General Elections in Nigeria. Our analysis is predicated on the conceptual relationship between elections and Democratic Development. We evaluated the conduct of the 2019 General Elections and noted that the elections were below the acceptable standards of a democratic election, wherefore the wide protestations that continually trialed the results. The paper also noted that the elections have once again brought to the fore some of the challenges threatening the survival of democracy in Nigeria. Finally, the paper argued that these challenges need to be addressed if the nation’s effort at democratic development is expected to produce meaningful results, particularly now as the nation is getting ready for another round of General Election in 2023.